Percepatan Pemulihan Ekonomi Pasca Pandemi Covid-19 Melalui Investasi Pasar Modal Syariah - Ahmad Agus Hidayat; Achmad Fageh; Siska Arie Novita; Elissa Qathrunnada; Fahmi Akhyar Al Farabi (Al-Buhuts, 2023)
The purpose of this research is to explore and examine the strategies being pursued to achieve economic recovery after the Covid-19 pandemic through the Islamic Capital Market Investment sector. The qualitative research method used in this study through a descriptive approach. While the analysis was used by conducting a deeper discussion based on the information obtained. The research results obtained are aimed at accelerating economic recovery after the Covid-19 pandemic by strengthening the Islamic economic and capital market system, strengthening public literacy regarding investment, increasing public trust in Islamic capital market products, and strengthening regulations on Islamic capital markets.